Cost and Schedule Comparison of Bauxite Soil Embankment Works for Open Storage Yard Development in the Futong Coastal Area, Siak, Indonesia - Ahmad Kurnain; Muhammad Yazid; Rahmat Tisnawan; Doni Rinaldi Basri (Lembaga Riset Ilmiah, 2026)
This study aims to analyze the comparative efficiency of cost and time in soil transportation using two methods: 300-foot barges and 250-foot barges, within a reclamation project. The research employs a descriptive quantitative method with a comparative approach to assess volume, cost, and completion time. The analysis indicates that using a 300-foot barge, with a transport capacity of 8,000 tons or approximately 3,810 m³ per trip, can complete a total workload of 1,000,000 m³ within 350 working days. The total cost for this method amounts to IDR 600 billion. In comparison, the 250-foot barge method requires a higher cost of IDR 650 billion for the same volume of work. Based on these calculations, the 300-foot barge method is deemed more efficient in both cost and time, offering a cost savings of IDR 50 billion and a more consistent execution timeline. The findings of this study are expected to serve as a reference for planning and decision-making regarding soil material transportation methods in future projects of similar scope.